2006
DOI: 10.1097/00124645-200611000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Retention in the Era of a Nursing Shortage

Abstract: Norton Healthcare has launched Norton Navigators, an 18-month mentoring program that matches recent nursing school graduates with experienced nurses. The program has improved Norton Healthcare's retention rate of new nurses and reduced the overall turnover rate for new graduates. Other benefits include saving 40,000 dollars per retained nurse, higher patient satisfaction, and an increase in recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…Beecroft et al (2006) distinguished the non-clinical, non-evaluative role of the resource person with the clinical supervisory role of the preceptor. Regardless of the title, this additional support person was intended to focus on the socialization of the new graduate (Zucker et al, 2006). There were an additional five studies that identified the use of a single resource person to support multiple new graduates as an alternate model of support.…”
Section: Common Features Of Transition Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beecroft et al (2006) distinguished the non-clinical, non-evaluative role of the resource person with the clinical supervisory role of the preceptor. Regardless of the title, this additional support person was intended to focus on the socialization of the new graduate (Zucker et al, 2006). There were an additional five studies that identified the use of a single resource person to support multiple new graduates as an alternate model of support.…”
Section: Common Features Of Transition Programsmentioning
confidence: 99%
“…All articles involving mentorship programs demonstrated enhanced new graduate nurse retention (Ho, 2006;Mills and Mullins, 2008). There was limited discussion of mentor selection criteria and matching (Fox, 2010), and only two articles discussed mentor training programs with little detail regarding the content delivered (Fox, 2010;Zucker et al, 2006). The effectiveness of mentor training, the selection process, and the matching process were not specifically assessed.…”
Section: Mentorshipmentioning
confidence: 99%
“…1 A structured program to teach time management strategies is also a key part of the development plan. At the weekly meetings, each participant identifies one or two goals to meet for their continued development, which fosters autonomy.…”
Section: Individualized Unit Orientationmentioning
confidence: 99%
“…The mentorship program implemented in this outcomes evaluation resulted in substantial improvements in nurse retention and turnover rates. Given that the average turnover rate for new graduates is 35% to 60% across the United States, this yields a substantial cost savings for the healthcare system as cost savings per retained nurse are estimated at approximately $40,000 (Zucker et al, 2006). Although this was not a randomized controlled trial with a placebo-control group, which substantially weakens the internal validity of the study, the outcomes clearly support the benefits of a mentorship program that focuses on topics that are not typically covered in traditional hospital orientation programs (e.g., communication, conflict and time management).…”
Section: Level Of Evidence: VImentioning
confidence: 99%